IMPLEMENTASI MODEL PEER TEACHING DALAM PEMBELAJARAN NAHWU DAN SHARAF DI MADRASAH ALIYAH - Lupiana, Indra; Supriyanto, Supriyanto (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
ABSTRACT This study aims to examine the implementation of the peer teaching model in two main branches of Arabic language learning, namely Nahwu and Sharaf, at Madrasah Aliyah Al Haitsam, Bogor. This innovation is part of a curriculum development initiative designed by the school principal to address difficulties in understanding the complex grammatical material of the Arabic language, as well as to provide a participatory space for senior students to serve as teaching assistants for their younger peers in this subject. This study employs a qualitative approach using the case study method. Data were collected through observation of the learning process at the school, in-depth interviews with the principal, subject teachers, student tutors, and tutored students, as well as documentation collected from various sources, including lesson plans, photos of activities, and school archives supporting this peer teaching activity. The results of the study indicate that the peer teaching model enhances students' understanding of Arabic grammatical concepts, strengthens active student engagement, fosters a collaborative learning environment, and develops leadership skills among senior students. This study recommends strengthening the training system for senior students and developing similar models for other subjects. ABSTRAK Penelitian ini bertujuan untuk mengkaji implementasi model peer teaching atau pengajaran sebaya dalam dua cabang utama pembelajaran bahasa Arab, yaitu Nahwu dan Sharaf di Madrasah Aliyah Al Haitsam, Kota Bogor. Inovasi ini merupakan bagian dari pengembangan kurikulum yang dirancang oleh kepala madrasah untuk mengatasi kesulitan siswa dalam memahami materi gramatikal bahasa Arab yang rumit, serta memberikan ruang partisipatif bagi siswa senior untuk menjadi asisten pengajar bagi adik kelas dalam mata pelajaran ini. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Data dikumpulkan melalui observasi dengan mengamati proses pembelajaran yang dilakukan di madrasah, kemudian wawancara mendalam dengan kepala madrasah, guru mata pelajaran, siwa yang menjadi tutor, dan siswa yang ditutor, serta dokumentasi yang dikumpulkan dari berbagai macam sumber seperti Rencana Pelaksanaan Pembelajaran (RPP), foto kegiatan, dan arsip sekolah yang mendukung kegiatan Peer Teaching ini. Hasil penelitian menunjukan bahwa model peer teaching meningkatkan pemahaman siswa terhadap konsep gramatikal bahasa Arab, memperkuat keterlibatan aktif siswa, membangun budaya belajar kolaboratif, serta membangun karakter kepemimpinan siswa senior. Penelitian ini merekomendasikan penguatan sistem pelatihan bagi siswa senior dan pengembangan model yang serupa untuk mata pelajaran lainnya.